Accelerated theta-burst transcranial magnetic stimulation of the bilateral dorsolateral prefrontal cortex in a patient with post-traumatic stress disorder and major depressive disorder: Case report - Chang, Chun-Hung; Liu, Chieh-Yu; Chen, Shaw-Ji; Tsai, Hsin-Chi (Frontiers in Psychiatry, 2023)
Background Theta-burst transcranial magnetic stimulation has demonstrated promising effectiveness as treatment for post-traumatic stress disorder (PTSD) and depression. However, the effect of accelerated theta-burst stimulation (TBS) in comorbid with PTSD and depression remains unknown. Case presentation We report a case of a 25-year-old woman with PTSD and depression whose symptoms markedly improved after continuous TBS of the right dorsolateral prefrontal cortex (DLPFC) and intermittent TBS (iTBS) over the left DLPFC, and then with 20 min break before the 2nd iTBS session. Conclusions Accelerated TBS over the bilateral DLPFC may improve severe PTSD and depression. Accelerated TBS may have more improvement of depression symptoms than PTSD symptoms. Further trials are warranted to investigate the effect and safety for patients with complicated PTSD and depression.